Dual blocade of the renin–angiotensin–aldosterone: does it always slow the progression of kidney disease? - Więcek, Andrzej; Nieszporek, Teresa; Zarzecki, Miłosz (Przewodnik Lekarza/Guide for GPs, 2010)
The RAS system has an important role in progression of chronic kidney disease. The inhibition of this system either with an ACE-I or ARB has been shown in clinical trails to be beneficial for renal protection. Dual blockade therapy of the RAS system (ACE-I and ARB) seems to have some benefit on blood pressure reduction, proteinuria and morbidity and mortality. However the results of recently published ONTARGET study has shown that ARB such as telmisartan is as effective as the ACE-I ramipril in preventing cardiovascular events in high risk patients. The combination of the two drugs has not shown benefits in renal outcomes. The decision whether to initiate dual RAS blockade for an individual patient, therefore requires careful assessment of their risk of renal progression.